RPA activates the XPF‐ERCC1 endonuclease to initiate processing of DNA interstrand crosslinks. (12th June 2017) - Abdullah, Ummi B; McGouran, Joanna F; Brolih, Sanja; Ptchelkine, Denis; El‐Sagheer, Afaf H; Brown, Tom; McHugh, Peter J
Abstract: During replication‐coupled DNA interstrand crosslink (ICL) repair, the XPF‐ERCC1 endonuclease is required for the incisions that release, or "unhook", ICLs, but the mechanism of ICL unhooking remains largely unknown. Incisions are triggered when the nascent leading strand of a replication fork strikes the ICL. Here, we report that while purified XPF‐ERCC1 incises simple ICL‐containing model replication fork structures, the presence of a nascent leading strand, modelling the effects of replication arrest, inhibits this activity. Strikingly, the addition of the single‐stranded DNA (ssDNA)‐binding replication protein A (RPA) selectively restores XPF‐ERCC1 endonuclease activity on this structure. The 5′–3′ exonuclease SNM1A can load from the XPF‐ERCC1‐RPA‐induced incisions and digest past the crosslink to quantitatively complete the unhooking reaction. We postulate that these collaborative activities of XPF‐ERCC1, RPA and SNM1A might explain how ICL unhooking is achieved in vivo . Synopsis: The endonuclease XPF‐ERCC1, implicated in DNA incision to "unhook" interstrand crosslinks (ICL) during replication‐coupled repair, can fulfill such a role on model substrates when acting in concert with single‐strand binding RPA and exonuclease SNM1A. XPF‐ERCC1 incises simple ICL‐containing model forks but is inhibited by fork structures containing nascent leading‐strand structures. RPA overcomes the inhibitory effect of a nascent leading strand. Exonuclease SNM1A can load at incisions made by XPF‐ERCC1‐RPA and digest past the ICL. Endonuclease activity of XPF‐ERCC1 and exonuclease activity of SNM1A act in concert to incise and unhook ICLs in vitro . Abstract : Unhooking of interstrand crosslinks on DNA structures mimicking arrested replication fork requires incision nuclease collaboration with replication protein A.